The Implementation of - Astiantih, Susi; Suryadi, Ray; Andas, Netty Huzniati; Pratiwi, Alifiah; Abin, Rais; Hafifah, Nurul (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
This research presented the Effect of Reading Wattpad Toward Students